Testate rhizopods as reliable, cost-effective indicators of environmental change - Scott, David B (Anuário do Instituto de Geociências, 2006)
This short paper summarizes some of the techniques that have been developed and perfected over the last 30 years for use as environmental indicators. Very few fossil groups provide the information that benthic foraminifera and thecamoebians can supply because their distributions and environmental preferences are fairly well known from a large amount of work that has been done on modern distributions and these associations can be used as proxies. In this brief paper several examples are given and briefly described where foraminifera and thecamoebians have been used for detecting sea-level change, pollution detection and monitoring, hurricane periodicity, earthquake precursors, paleoclimate studies and freshwater/marine transitions.